2020
DOI: 10.1186/s12884-020-2829-y
|View full text |Cite
|
Sign up to set email alerts
|

OptiBIRTH: a cluster randomised trial of a complex intervention to increase vaginal birth after caesarean section

Abstract: Background: Despite evidence supporting the safety of vaginal birth after caesarean section (VBAC), rates are low in many countries. Methods: OptiBIRTH investigated the effects of a woman-centred intervention designed to increase VBAC rates through an unblinded cluster randomised trial in 15 maternity units with VBAC rates < 35% in Germany, Ireland and Italy. Sites were matched in pairs or triplets based on annual birth numbers and VBAC rate, and randomised, 1:1 or 2:1, intervention versus control, following t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Willingness to change was added as it becomes and overarching factor across qualitative evidence syntheses [ 28 , 86 ] and discussion section of trials reports [ 34 , 44 ] – where both providers and trialists mentioned that the underlying factor of success lies on providers’ beliefs about CS and vaginal birth, as well as whether providers are willing to step out of their comfort zone to change Individual dissemination of audit and feedback results: dissemination of audit and feedback results to providers individually instead in group settings Internal policies that support vaginal birth: whether internal policies that support vaginal birth or the intervention exists outside of the intervention. This include national consensus in improving CS rates where CS is nationally treated as a measure of institutional and individual practice quality [ 44 ], recommended maternity practices supporting physiologic birth [ 39 , 41 , 43 , 45 ], national guidelines on vaginal birth after caesarean (VBAC) [ 67 ], equipment and technical support for local healthcare facilities [ 63 ], implementation of new care models favouring physiologic birth [ 65 ], additional rooms to support physiologic birth [ 65 ], hire full-time obstetricians [ 34 ], and increase staffing in the labour ward [ 34 ] Multidisciplinary collaboration: when the intervention involved different cadre of health workers in caring for women, which could include team of obstetricians, midwives, nurses, and doctors working together Reflective nature of intervention: Leveraged bottom-up approach through discussions and consultations Training to improve providers’ knowledge and skills : implementation of theory-based or practical education session for healthcare providers to improve their knowledge and skills on labour management …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Willingness to change was added as it becomes and overarching factor across qualitative evidence syntheses [ 28 , 86 ] and discussion section of trials reports [ 34 , 44 ] – where both providers and trialists mentioned that the underlying factor of success lies on providers’ beliefs about CS and vaginal birth, as well as whether providers are willing to step out of their comfort zone to change Individual dissemination of audit and feedback results: dissemination of audit and feedback results to providers individually instead in group settings Internal policies that support vaginal birth: whether internal policies that support vaginal birth or the intervention exists outside of the intervention. This include national consensus in improving CS rates where CS is nationally treated as a measure of institutional and individual practice quality [ 44 ], recommended maternity practices supporting physiologic birth [ 39 , 41 , 43 , 45 ], national guidelines on vaginal birth after caesarean (VBAC) [ 67 ], equipment and technical support for local healthcare facilities [ 63 ], implementation of new care models favouring physiologic birth [ 65 ], additional rooms to support physiologic birth [ 65 ], hire full-time obstetricians [ 34 ], and increase staffing in the labour ward [ 34 ] Multidisciplinary collaboration: when the intervention involved different cadre of health workers in caring for women, which could include team of obstetricians, midwives, nurses, and doctors working together Reflective nature of intervention: Leveraged bottom-up approach through discussions and consultations Training to improve providers’ knowledge and skills : implementation of theory-based or practical education session for healthcare providers to improve their knowledge and skills on labour management …”
Section: Resultsmentioning
confidence: 99%
“…Due to an imbalance of successful and unsuccessful interventions in financial reform group (two successful [54,55], 9 unsuccessful [47-53, 56, 57]), and a limited number of studies using interventions other than audit and feedback and financial reform (6/32 studies) [23,[58][59][60][61][62], these interventions could not be analysed (as QCA requires similar number of successful and unsuccessful interventions, typically at least 10 cases to be compared). Therefore, this QCA is based only on 15 audit and feedback interventions [22,[33][34][35][36][37][38][39][40][41][42][43][44][45][46] and six multi-target interventions [63][64][65][66][67][68].…”
Section: Identifying Data Sources and Selecting Casesmentioning
confidence: 99%
“…A recent study Open access on preterm infants showed that a preterm trial of labour did not increase the risk for neonatal morbidity when compared with planned repeat CS in women without previous vaginal birth. 16 Rates of repeat planned CS vary depending on both clinical and non-clinical factors, like different hospital practice 17 and guidelines for management of birth after a previous CS differ substantially. 18 In Sweden, where this study was carried out, women do not have the right automatically to opt for a CS in the absence of medical or obstetric reasons for a CS.…”
Section: Open Accessmentioning
confidence: 99%
“…12,15 Few studies have evaluated the effects of clinician-centered interventions to promote VBAC, and the available data show conflicting results. 16,17 A systematic review on this topic reported that the only strategy that significantly increased VBAC rates was an educational intervention provided by an opinion leader. 15 Moreover, interventions such as audit feedback, quality improvement, and multifaceted strategies are effective ways to change clinical practice and reduce the rate of CS.…”
Section: Introductionmentioning
confidence: 99%